A Proposed Model of Intercultural Communication Competence (ICC) in Malaysian Context - Nadeem, Muhammad Umar; Mohammed, Rosli; Dalib, Syarizan (DergiPark Akademik, 2017)
The basic determination for this paper is to throw light on the culture general models of intercultural communication competence (ICC). Furthermore, to propose a culture general model for Malaysian context in the presence of religiosity.It is suggested by the previous researchers to refine these models by adding variables in them.Ministry of Higher Education of Malaysia is hosting huge number of international students in their institutions and have plans to host maximum from the whole world.Religion is the key element of intercultural interactions in Malaysia.Therefore, a research on the international students in the context of religion would provide the better understanding and application of culture general model of ICC in Malaysian context.As well as, it will provide valuable findings that depicts to what extent the religiosity of international students enables them to be competent in intercultural communication.